Bank Emok in the Perceptions of Barudua Villagers and its Relation to Hadith Threats to Usury Perpetrators - Kinkin Syamsudin (Institut Ilmu Keislaman Zainul Hasan Genggong, 2023)
This article tries to capture about the emok bank phenomenon that is rife among the residents of Barudua Village. The type of data used in this study is a type of qualitative data. The data studied were collected through literature review, interviews and direct observations in the field. This article focuses on two things; whether emok bank is part of the usury practice and how the residents of Barudua Village perceive emok bank. By analyzing various hadith literature that describes sin and threats to usury perpetrators, it is concluded that the emok bank loved by the residents of Barudua Village is part of the practice of usury. Meanwhile, the perception and attitude of the residents of Barudua Village towards emok bank itself is influenced by their mindset and lack of religious understanding of usury with its various models and forms.